Extracellular matrix cues regulate the differentiation of pluripotent stem cell-derived endothelial cells - Noh, Kyung Mu; Park, Soon-Jung; Moon, Sung-Hwan; Jung, Seok Yun (Frontiers in Cardiovascular Medicine, 2023)
The generation of endothelial cells (ECs) from human pluripotent stem cells (PSCs) has been a promising approach for treating cardiovascular diseases for several years. Human PSCs, particularly induced pluripotent stem cells (iPSCs), are an attractive source of ECs for cell therapy. Although there is a diversity of methods for endothelial cell differentiation using biochemical factors, such as small molecules and cytokines, the efficiency of EC production varies depending on the type and dose of biochemical factors. Moreover, the protocols in which most EC differentiation studies have been performed were in very unphysiological conditions that do not reflect the microenvironment of native tissue. The microenvironment surrounding stem cells exerts variable biochemical and biomechanical stimuli that can affect stem cell differentiation and behavior. The stiffness and components of the extracellular microenvironment are critical inducers of stem cell behavior and fate specification by sensing the extracellular matrix (ECM) cues, adjusting the cytoskeleton tension, and delivering external signals to the nucleus. Differentiation of stem cells into ECs using a cocktail of biochemical factors has been performed for decades. However, the effects of mechanical stimuli on endothelial cell differentiation remain poorly understood. This review provides an overview of the methods used to differentiate ECs from stem cells by chemical and mechanical stimuli. We also propose the possibility of a novel EC differentiation strategy using a synthetic and natural extracellular matrix.